The Influence of Lifestyle, Korean Wave, and Brand Image on Merchandise Purchase Decisions at Kwangya Café (Case Study: Lotte Shopping Avenue, South Jakarta)” - Finiola Widianingrum; Surya Fadja Boediman; Saptarining Wulan; Rahmat Ingkadijaya (International Journal of Travel, Hospitality and Events, 2026)
The popular culture-driven tourism sector in Indonesia has grown remarkably due to the widespread influence of the Korean Wave, which has reshaped the lifestyle and spending habits of younger generations. Nevertheless, scholarly research that holistically examines how lifestyle, Korean Wave exposure, and brand image jointly affect merchandise buying behavior at Korean-themed cafes remains scarce. This study investigates the impact of these three variables on merchandise purchase decisions at Kwangya Café, Lotte Shopping Avenue, South Jakarta, analyzing both individual and combined effects. A quantitative survey method was employed, and 100 respondents were chosen by purposive sampling according to criteria aimed at young tourists who are enthusiastic about Korean culture. A standardized Likert-scale questionnaire was used to collect the data, and SPSS version 26 was used to perform multiple linear regression analysis. The findings indicated that purchase decisions were positively and statistically significantly impacted by lifestyle (β = 0.199; sig. 0.010), Korean Wave (β = 0.361; sig. 0.000), and brand image (β = 0.381; sig. 0.000). Together, the three variables showed a substantial influence, with an explanatory power of 81.8% (Adjusted R² = 0.818) and an F-value of 163.924. The most important aspect was found to be brand image. In addition to offering practical suggestions for business stakeholders and legislators looking to maximize the potential of Korean Wave-inspired cultural tourism in Indonesia, this study theoretically adds to the expanding body of research on popular culture-based consumer behavior in the tourism sector..